2009
DOI: 10.1303/aez.2009.1
|View full text |Cite
|
Sign up to set email alerts
|

Arthropods as bioindicators of sustainable forest management, with a focus on plantation forests

Abstract: Here we review the bioindicator potentials of several arthropod groups in forest management. First, we describe the indicator potentials of frequently used arthropod groups in general forest management, and then evaluate ecosystem function and plural taxonomic groups to infer forest biodiversity. We then review indicator potentials of arthropod groups to explore the ecological consequences of forest management practices. Different arthropod groups respond differently to forest management. Ants, carabid beetles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 120 publications
6
94
0
5
Order By: Relevance
“…Unfortunately, temperate forests are being converted into monoculture plantations and agricultural land, increasing the dominance of human activity on the landscape; the resulting fragmentation of forests has caused a marked decrease in biodiversity (Kimmins 1997;Maleque et al 2006). Particularly, it has been suggested that canopy arthropods can be considered indicators of forest condition because they respond quickly to changes in environmental conditions (Schowalter 1995;Ozanne et al 1997;Maleque et al 2006Maleque et al , 2009.…”
Section: Disturbancesmentioning
confidence: 99%
“…Unfortunately, temperate forests are being converted into monoculture plantations and agricultural land, increasing the dominance of human activity on the landscape; the resulting fragmentation of forests has caused a marked decrease in biodiversity (Kimmins 1997;Maleque et al 2006). Particularly, it has been suggested that canopy arthropods can be considered indicators of forest condition because they respond quickly to changes in environmental conditions (Schowalter 1995;Ozanne et al 1997;Maleque et al 2006Maleque et al , 2009.…”
Section: Disturbancesmentioning
confidence: 99%
“…Serving as surrogates for more inclusive fractions of biodiversity, moth inventory data can be related to various environmental parameters. For example, moth community studies have addressed aspects such as effects of logging, habitat conversion and the effects of succession or fragmentation on insect biodiversity (Intachat et al, 1999;Fiedler & Schulze, 2004;New, 2004;Schmidt & Roland, 2006;Fiedler et al, 2007;Maleque et al, 2009). All these inventories rely exclusively on samples collected by light traps.…”
Section: Attraction Radius Of Light Trapsmentioning
confidence: 99%
“…On one hand, downed small and medium diameter dead wood should be given greater consideration when planning conservation mea sures for saproxylic organisms. On the other hand, given the ease of sampling, the validity of the fraction of wood debris used in this study needs to be tested as an indicator of sustainable forest management (Similä et al, 2006;Maleque et al, 2009).…”
Section: Discussionmentioning
confidence: 99%